STUDY THE N - ACETYLCYSTEINE EFFECTS ON GASTRECTOMY AND SOME BIOCHEMICAL PARAMETERS IN DOGS - Ashraff Waleed Abdulrazaq et al., (Basrah Journal of Veterinary Research)
The project of research was carrying out to study the effect of N-acetylcysteine on thewounds which developed in the stomach after gastrotomy. Dogs were used in this study asexperimental animals. Dogs were divided into two groups' treatment and control; each groupcontains 5 animals. The surgical incision was closed by two layers of sutures using absorbentsutures then closed the muscle and skin using traditional steps. The treatment group was treatedusing 3% of N-acetylcysteine fluid topically on site of operation, as well as N-acetylcysteine(140 mg/kg/ day) was administrated orally for 7 days. Gross examination and clinical signswere recorded after 7 days of operation. Blood samples were collected before the surgery and 7days after the surgery for complete blood studies on blood samples in both groups.Additionally, tissue samples were taken from operation areas to study the histological change.Results of this study show that the healing of treated groups with N-acetylcysteine wasdisappeared after 3 days while in control groups the healing sings continued until 7 days aftersurgery. The mucous membranes in the group treated with N-acetylcysteine were healthiercomparative to the control group after 7 days of operation. Openings of the surgical area in thecontrol group suffered from adhesions led to hemorrhage during their separation while in thetreated group there were no adhesions. Blood analysis and liver enzymes tests showed anabsence of inflammation and regularity of all liver enzymes in the treated group. Finally, the treated groups showed the normal arrangement of tissue layers and no adhesion or increasing incollagen fibers.